Detection of aspergillus DNA in cerebrospinal fluid from patients with cerebral aspergillosis by a nested PCR assay - Hummel, Margit; Spiess, Birgit; Kentouche, K.; Niggemann, S.; Böhm, C.; Reuter, S.; Kiehl, M.; Mörz, Handan; Hehlmann, Rüdiger; Buchheidt, Dieter (Journal of clinical microbiology, 2006)
Invasive aspergillosis (IA), a complication with high mortality rates, especially in disseminated IA with cerebral involvement, is difficult to diagnose. Biopsy of cerebral lesions is often not feasible, and culture of Aspergillus spp. from cerebrospinal fluid (CSF) is frequently negative. New molecular methods have emerged for diagnosing IA. So far, there are only few reports of Aspergillus DNA detection in CSF. After modifying the DNA extraction protocol, we detected Aspergillus DNA in CSF samples by a previously described nested PCR assay. In six patients with hematologic malignancy and cerebral aspergillosis, CSF samples were investigated for Aspergillus DNA. IA was classified according to the EORTC/MSG 2002 criteria. Two patients each had proven, probable, and possible IA. Thirty-five CSF samples were investigated for Aspergillus DNA by nested PCR. Samples with positive results in the nested PCR assay were quantified by LightCycler PCR assay. Fourteen CSF samples showed positive results in the nested PCR assay. Of these, six samples gave positive results in real-time PCR. The range of CFU per ml was 2,154 to 63,100,000. The highest number of CFU per ml was found in a CSF sample of a patient with acute lymphocytic leukemia and probable cerebral aspergillosis. Detection of Aspergillus DNA in CSF samples is thus possible and has the potential to improve diagnosis of cerebral aspergillosis. Further prospective studies with larger numbers of patients must be performed to evaluate the clinical significance of Aspergillus PCR with CSF samples.
Gesehen am 10.05.2022